The dual PI3K/mTOR inhibitor NVP‐BEZ235 and chloroquine synergize to trigger apoptosis via mitochondrial‐lysosomal cross‐talk. Issue 11 (4th December 2012) - Seitz, Christian; Hugle, Manuela; Cristofanon, Silvia; Tchoghandjian, Aurélie; Fulda, Simone
Abstract: On the basis of our previous identification of aberrant phosphatidylinositol‐3‐kinase (PI3K)/Akt signaling as a novel poor prognostic factor in neuroblastoma, we evaluated the dual PI3K/mTOR inhibitor BEZ235 in the present study. Here, BEZ235 acts in concert with the lysosomotropic agent chloroquine (CQ) to trigger apoptosis in neuroblastoma cells in a synergistic manner, as calculated by combination index (CI < 0.5). Surprisingly, inhibition of BEZ235‐induced autophagy is unlikely the primary mechanism of this synergism as reported in other cancers, since neither inhibition of autophagosome formation by knockdown of Atg7 or Atg5 nor disruption of the autophagic flux by Bafilomycin A1 (BafA1) enhance BEZ235‐induced apoptosis. BEZ235 stimulates enlargement of the lysosomal compartment and generation of reactive oxygen species (ROS), while CQ promotes lysosomal membrane permeabilization (LMP). In combination, BEZ235 and CQ cooperate to trigger LMP, Bax activation, loss of mitochondrial membrane potential (MMP) and caspase‐dependent apoptosis. Lysosome‐mediated apoptosis occurs in a ROS‐dependent manner, as ROS scavengers significantly reduce BEZ235/CQ‐induced loss of MMP, LMP and apoptosis. There is a mitochondrial‐lysosomal cross‐talk, since lysosomal enzyme inhibitors significantly decrease BEZ235‐ and CQ‐induced drop of MMP and apoptosis. In conclusion, BEZ235 and CQ act in concert to trigger LMP and lysosome‐mediated apoptosis via a mitochondrial‐lysosomal cross‐talk. These findings have important implications for the rational development of PI3K/mTOR inhibitor‐based combination therapies. Abstract : What's new? Defects in apoptosis can contribute to tumor formation and treatment resistance. The PI3K/Akt/mTOR pathway inhibits apoptosis, and is highly activated in most human cancers. Aberrant PI3K/Akt signaling is also a novel poor prognostic factor in neuroblastoma. In this study, the authors evaluated the dual PI3K/mTOR inhibitor BEZ23520 in combination with chloroquine. They found that, together, these drugs act synergistically to trigger lysosome‐mediated apoptosis in neuroblastoma cells, via mitochondrial‐lysosomal cross‐talk. These findings may lead to the rational development of inhibitor‐based combination therapies directed against PI13K/mTOR.